Sound-localization deficits induced by lesions in the barn owl's auditory space map - Wagner, H (J Neurosci, 1993)
Barn owls possess a two-dimensional map of auditory space. The map appears in its final form in the external nucleus of the inferior colliculus (ICx) and is projected from there to the optic tectum (OT). To determine the role of the map in ICx or its projected version in OT in the localization of acoustic stimuli, head movements of three adult owls were recorded before and after lesioning parts of the map either in ICx or in OT. Small electrolytic lesions caused sound-localization deficits that were characterized by failures to turn, turns away from the sound source, increased response latencies, and reduced turning amplitudes. These deficits occurred at azimuths expected from the physiological data obtained at the lesion site before passing current. They extended over an azimuthal range of some 20 degrees. Thus, this is the first unambiguous demonstration, for sound localization, of a deficit covering a well circumscribed area within an auditory hemifield. Since the major lesion deficits were restricted to one hemifield, a second lesion was made in the space map of the other side of the brain in each animal. The second lesion resulted in behavioral deficits qualitatively similar to those produced by the first lesion. In total, the study is based on nine lesions, three in each owl. Two lesions were sham lesions. These and two further lesions did not produce a measurable deficit. In four of the five remaining cases, in which a behavioral deficit was observed initially, the behavioral performance recovered with time. In two cases, the deficit disappeared completely. Although improvement occurred also in the remaining two cases, prelesion response amplitudes were not reached in one case, and response latency did not reach prelesion values in the other case. Because the behavioral deficits induced by the second lesions disappeared in the same way as did the deficits induced by the first lesions, the possibility is excluded that the animals learned to respond tactically, that is, that they learned to associate “unlocatable sounds” with the lesioned side. The deficits were also not due to a generalized motor impairment, because immediately after the lesion the animals responded as they did before the lesion to stimulation from outside the well circumscribed affected region of space. The possibility is discussed that plasticity after small central (neural) injuries is maintained longer in the lifetime of an animal than plasticity after peripheral (mechanical) manipulations.